2012
DOI: 10.5505/agri.2012.38258
|View full text |Cite
|
Sign up to set email alerts
|

The risk factors of patient's have low back pain applied to policlinic of Algology department

Abstract: Lower education, lower economic level, labor intensive jobs and smoking were correlated with lower back pain. It was concluded that by taking precautions that lower risk factors, incidence of lower back pain can be decreased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…On the other hand, in our study, 89.2% of the participants did not use alcohol. Ayvat et al reported that there was no relationship between alcohol intake and LBP [13]. Again this research supports our findings.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…On the other hand, in our study, 89.2% of the participants did not use alcohol. Ayvat et al reported that there was no relationship between alcohol intake and LBP [13]. Again this research supports our findings.…”
Section: Discussionsupporting
confidence: 91%
“…According to one study, 45.9% of people with LBP were housewives [7]. In fact, Ayvat et al reported that even 52.5% of patients with LBP were housewives [13]. In this study, we found similar results.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In this study, the smoking rate was 38%. In the literature, just as there are studies showing a correlation between smoking and low back pain (21,23,24,25), there are studies showing no correlation (15,20,26). Studies proposing no effect of smoking on low back pain give reasons such as nicotine's analgesic effect and depression-reducing effects of nicotine; studies stating that there is an association indicate that smoking increases the risk of low back pain incidence due to disrupting nutrition of the vertebral disk, making the disk more susceptible to external factors, and reducing blood perfusion in the spine and muscles due to vasoconstriction caused by nicotine in cigarettes (23).…”
Section: Discussionmentioning
confidence: 99%